2014
DOI: 10.3920/bm2013.0031
|View full text |Cite
|
Sign up to set email alerts
|

Propionic acid and its esterified derivative suppress the growth of methicillin-resistant Staphylococcus aureus USA300

Abstract: Previously, we demonstrated that Propionibacterium acnes, a human skin commensal bacterium, ferments glycerol into short-chain fatty acids, including propionic acid. Propionic acid suppressed the growth of Staphylococcus aureus USA300, a community-acquired methicillin-resistant bacterium, in vitro and in vivo. In this study, it is demonstrated that the anti-USA300 activity of propionic acid persisted after buffering the acid with 4-(2-hydroxyethyl)-1- piperazineethanesulfonic acid. This suggests that the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 52 publications
1
62
0
Order By: Relevance
“…As shown in Figure 3, four SCFAs were produced in the fermented media of S. epidermidis . Results in our previous papers demonstrated that pH buffering does not influence the antimicrobial activities of SCFAs [15]. Furthermore, SCFAs can passively diffuse through the cell wall of bacteria and kill bacteria by lowering the intracellular pH [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3, four SCFAs were produced in the fermented media of S. epidermidis . Results in our previous papers demonstrated that pH buffering does not influence the antimicrobial activities of SCFAs [15]. Furthermore, SCFAs can passively diffuse through the cell wall of bacteria and kill bacteria by lowering the intracellular pH [8].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that a co-drug—butyric acid 2-(2-butyryloxyethoxy) ethyl ester—can release two active butyric acids in mice (data not shown). A co-drug—propionic acid 2-(2-propionyloxy-ethoxy)-ethyl ester—exerts antimicrobial activity [15]. Application of these co-drugs onto acne lesions may conquer the drawbacks of SCFAs with short half-lives for acne treatments.…”
Section: Discussionmentioning
confidence: 99%
“…7 Additionally, metabolites of adult-associated skin commensals can decrease skin pH and enhance antimicrobial activities, thus suppressing adherence and growth of S. aureus in human keratinocytes. 4, 8, 9 …”
Section: To the Editormentioning
confidence: 99%
“…However, measurements in other, more easily accessible organs (e.g., the colon), where fermenting bacterial species are present suggests that PA levels can be as high as 20-140 mM (Garland SH 2001). These concentrations are sufficient to control pathogenic microbes: minimal bactericidal or fungicidal PA concentrations for different species were found to be 10-25 mM (Wang Y 2014). Based on these data, we chose PA concentrations of 1-10mM for our in vitro experiments that was in a range often used by other investigators (Allaker RP 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PA exhibits antimicrobial properties that may be independent of its acidic nature (Wang Y 2014). High PA concentrations, however, may also have deleterious effects, leading to cellular damage and, thus, compromising the integrity of the epidermal barrier.…”
Section: Discussionmentioning
confidence: 99%